PERAN PIMPINAN DALAM MEMBERDAYAKAN TENAGA PENDIDIK UNTUK MEMBANGUN GOOD UNIVERSITY GOVERNANCE - R. AR Harry Anwar (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2019)
The head of the higher education institution does not only play the role of administrator, manager, and supervisor of the programs established by the institution. The role of the head of the higher education institution to be a leader of the higher education institution must be able to grow the effectiveness of the planned program, be innovative in making decisions, as well as efficient in terms of time management, especially in terms of empowering educators. All of this must be internalized within the leadership of higher education institutions in building Good University Governance. This study uses qualitative research methods based on literature studies. The role of leadership in empowering educators to build Good University Governance will not be separated from its success in applying discipline, communication, participation, and building a professional work culture. Leaders of higher education institutions not only play roles as administrators, leaders, managers, or supervisors, but are holistically demanded to play an active role in internalizing strong responsibilities, as leadership capital capable of empowering teaching staff, effectively and measurably.